Free Tissue Transfer for Upper Extremity Reconstruction - Dibbs, Rami; Grome, Luke; Pederson, William C. (Seminars in Plastic Surgery, 2019)
With the advent of the Industrial Revolution, traumatic injuries of the upper extremity increased exponentially. As a result, surgeons began to reevaluate amputation as the standard of care. Following the Second World War, local and regional pedicled flaps became common forms of traumatic upper extremity reconstruction. Today, microsurgery offers an alternative when options lower on the reconstructive ladder have been exhausted or will not produce a desirable result. In this article, the authors review the use of free tissue transfer for upper extremity reconstruction. Flaps are categorized as fasciocutaneous, muscle, and functional tissue transfers. The thin pliable nature of fasciocutaneous flaps makes them ideal for aesthetically sensitive areas, such as the hand. The radial forearm, lateral arm, scapula, parascapular, anterolateral thigh, and temporoparietal fascia flaps are highlighted in this article. Muscle flaps are utilized for their bulk and size; the latissimus dorsi flap serves as a “workhorse” free muscle flap for upper extremity reconstruction. Other muscle flaps include the rectus abdominis and serratus anterior. Lastly, functional tissue transfers are used to restore active range of motion or bony integrity to the upper extremity. The innervated gracilis can be utilized in the forearm to restore finger flexion or extension. Transfer of vascularized bone such as the fibula may be used to correct large defects of the radius or ulna. Finally, replacement of “like with like” is embodied in toe-to-thumb transfers for reconstruction of digital amputations.
Keywords: upper extremity reconstruction; free flap; fasciocutaneous flap; muscle flap; functional tissue transfer